The Application of Folktale Film to Improve Teaching Writing Narrative Text by Using Discovery Learning for Grade X MIPA-B Semester 2 at SMA Negeri 1 Probolinggo Year 2019/2020 - Saiful Bahri (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
Writing in English is not easy for the students. They sometimes face difficulties to make writing in English so they feel bored and consider that the writing activities are not interesting and difficult. Therefore, the use of film can give advantageous for them especially in teaching writing. Therefore, the writer tried to use folktale movie viewing in teaching narrative texts for Grade MIPA-B Semester 1 At SMA Negeri 1 Probolinggo. In this study, the researcher used an action research design. Action research is a specific type of applied research, its purpose is to solve a specific classroom problem or make a decision at a single local site. The Result of Students’ Narrative Writing in Term Content of The First Cycle from 32 students are 2 students get excellent, 30 students get good level, four students get fair level, and no students get poor level. The Result of Students’ Narrative Writing in Term Organization of The First Cycle are 2 students get excellent, 36 students get good level, 1 student gets fair level. And no students get poor level. Based on the questionnaire filled by students in X MIA-B that consists of 32 students, The result of students’ responses to the application of using folktale film to teach narrative text in writing skill can be described that 64 % students get interesting to the film and 75% students are able to write well, Folktale Film Viewing In Teaching Narrative Text, the researcher concluded that this film can be used as an alternative in improving teaching narrative text and the researcher should continue to the second cycle in order to get the students improvement in writing ability<./p>